2009
DOI: 10.3340/jkns.2009.46.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Hemorrhage : Classification and Related Factors

Abstract: Objective : Clinical features of pituitary hemorrhage vary from asymptomatic to catastrophic. The purpose of this study was to evaluate the factors related to severity of hemorrhage of pituitary adenoma. Methods : Pituitary hemorrhage was noted in 32 of 88 patients who underwent operations between January 2000 and December 2007. Clinical status was classified into group I (no hemorrhage symptoms), II (mild to moderate symptoms without neurological deficit), and III (with neurological deficit), and was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…SPAH was common in the patients with prolactinomas (46·8%), whereas CPAA was common in the patients with nonfunctioning pituitary adenomas (100%). These results coincide well with the data of previous studies, in which the incidence of SPAH has been reported to range from 9·5 to 18·1% and prolactinomas have been found to be the most frequent tumours in patients with pituitary adenomas with subclinical haemorrhage . On the other hand, CPAA is known to frequently occur in patients with nonfunctioning adenomas (66·7–84·4%) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SPAH was common in the patients with prolactinomas (46·8%), whereas CPAA was common in the patients with nonfunctioning pituitary adenomas (100%). These results coincide well with the data of previous studies, in which the incidence of SPAH has been reported to range from 9·5 to 18·1% and prolactinomas have been found to be the most frequent tumours in patients with pituitary adenomas with subclinical haemorrhage . On the other hand, CPAA is known to frequently occur in patients with nonfunctioning adenomas (66·7–84·4%) .…”
Section: Discussionsupporting
confidence: 92%
“…These results coincide well with the data of previous studies, in which the incidence of SPAH has been reported to range from 9Á5 to 18Á1% 2,4,14-16 and prolactinomas have been found to be the most frequent tumours in patients with pituitary adenomas with subclinical haemorrhage. 2,4,14 On the other hand, CPAA is known to frequently occur in patients with nonfunctioning adenomas (66Á7-84Á4%). 4,17,18 The differences in features of SPAH in patients with prolactinomas and CPAA in patients with nonfunctioning adenomas remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with the previous observation that the occurrence of fluid-fluid levels within hemorrhagic pituitary tumors ranges from 48.1-55.8% (10,14). Additionally, hemorrhage within pituitary adenomas is common in patients with non-functioning adenomas and prolactinomas (9,(16)(17)(18)(19)(20)(21); although an earlier study suggests that GH-and ACTH-secreting pituitary adenomas are more likely to present apoplexy than others (22). This immunological variation may be due to the lack of specific clinical markers for non-functioning and FSH/LH tumors, which may remain undetected for many years until they become large enough to induce tumor ischemia (13,21).…”
Section: Discussionsupporting
confidence: 82%
“…In PRL and multi-functional pituitary adenomas, hemorrhage and cystic degeneration may occur due to high metabolism and relative ischemia (19). In addition, it is notable that large or rapidly growing pituitary adenomas maybe prone to hemorrhage and cyst formation (17).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 88 cases of macroadenoma by Kim et al .,[ 14 ] hemorrhage was detected in 36% cases. In another study of 83 cases by Nishi et al .,[ 15 ] hemorrhage was detected in 31% cases.…”
Section: Discussionmentioning
confidence: 99%